2020
DOI: 10.1103/physrevd.101.083020
|View full text |Cite
|
Sign up to set email alerts
|

DAMA/LIBRA annual modulation and axion quark nugget dark matter model

Abstract: The DAMA/LIBRA experiment shows 9.5σ evidence for an annual modulation in the (1 − 6) keV energy range, strongly suggesting that the observed modulation has the dark matter origin. However, the conventional interpretation in terms of WIMP-nucleon interaction is excluded by other experiments. We propose an alternative source of modulation in the form of neutrons, which have been liberated from surrounding material. Our computations are based on the so-called Axion Quark Nugget (AQN) dark matter model, which was… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 92 publications
(277 reference statements)
1
28
0
Order By: Relevance
“…(8) dark matter. Other types of dark matter including composite candidates capable of producing single events in mechanical oscillators or phonons in crystals; (9) axion quark nuggets [47] are claimed to be able to produce seismic and acoustic waves in planet's atmosphere [48] as well as explain sum other anomalies such as Sun's corona anomaly [49] and DAMA/LIBRA results [50] as well as others. The axion quark nugget events described in the work with the alleged detection [48] can be ruled out based on the same points as for atmospheric meteor events.…”
Section: Introductionmentioning
confidence: 99%
“…(8) dark matter. Other types of dark matter including composite candidates capable of producing single events in mechanical oscillators or phonons in crystals; (9) axion quark nuggets [47] are claimed to be able to produce seismic and acoustic waves in planet's atmosphere [48] as well as explain sum other anomalies such as Sun's corona anomaly [49] and DAMA/LIBRA results [50] as well as others. The axion quark nugget events described in the work with the alleged detection [48] can be ruled out based on the same points as for atmospheric meteor events.…”
Section: Introductionmentioning
confidence: 99%
“…The AQNs may also offer a resolution of the "Primordial Lithium Puzzle" [44] and the longstanding puzzle with the DAMA/LIBRA observation of the annual modulation at 9.5σ confidence level [45]. Furthermore, it may resolve the observed (by XMM-Newton at 11σ confidence level [46]) puzzling seasonal variation of the X-ray background in the near-Earth environment in the 2-6 keV energy range as suggested in [47].…”
Section: Discussionmentioning
confidence: 87%
“…An analysis of the initial 59.5 days of COSINE-100 data showed that the annual modulation signal reported by DAMA is inconsistent with the explanation using SI interaction between WIMPs and sodium or iodine nuclei in the context of the standard halo model (SHM) ( 21 ). However, this first result left open interpretations using certain alternative dark matter models ( 23 , 24 ), dark matter halo distributions ( 25 ), and detector responses ( 25 , 26 ) that could allow room for consistency between DAMA and COSINE-100. Model-independent searches of an annual modulation signal using 1.7-years data were also reported but were still not sensitive enough to conclusively challenge the DAMA observation ( 22 ).…”
Section: Introductionmentioning
confidence: 99%